First Psychotic Episode in a Patient with DiGeorge Syndrome and Selective Mutism - Coutinho, Francisco (2020)
DiGeorge Syndrome is a group of diseases caused by a microdeletion, and some of its most frequent symptoms are those related with development and behavior. We present the case of a female patient with DiGeorge Syndrome and selective mutism since childhood, evaluated for the first time in a psychiatry consultation at the age of 18 for inaugural psychotic symptomatology. We describe the psychopathology, the diagnostic investigation, the treatment, and the clinical evolution. In the future, it will be important to better characterize patients with this syndrome who present psychiatric disease.